The Role of Glycosphingolipids in Immune Cell Functions - Zhang, Tao; de Waard, Antonius A.; Wuhrer, Manfred; Spaapen, Robbert M. (Frontiers in Immunology, 2019)
Glycosphingolipids (GSLs) exhibit a variety of functions in cellular differentiation and interaction. Also, they are known to play a role as receptors in pathogen invasion. A less well explored feature is the role of GSLs in immune cell function which is the subject of this review article. Here we summarize knowledge on GSL expression patterns in different immune cells. We review the changes in GSL expression during immune cell development and differentiation, maturation and activation. Furthermore, we review how immune cell GSLs impact membrane organization, molecular signaling and trans-interactions in cellular cross-talk. Another aspect covered is the role of GSLs as targets of antibody-based immunity in cancer. We expect that recent advances in analytical and genome editing technologies will help in the coming years to further our knowledge on the role of GSLs as modulators of immune cell function.